Vitamin D Deficiency in Lebanese Adults: Prevalence and Predictors from a Cross-Sectional Community-Based Study - Asma Arabi; Nariman Chamoun; Mona P. Nasrallah; Hani M. Tamim (International Journal of Endocrinology)
Background/Objectives. The prevalence of vitamin D deficiency in the Middle Eastern population remains among the highest in the world, despite the region enjoying sunlight most days of the year. This study aimed at assessing the status of serum vitamin D and determining factors associated with vitamin D deficiency among community-dwelling adults residing in Greater Beirut, Lebanon. Methods. A random sample of Lebanese adults residing in the Greater Beirut area was selected based on area probability and multistage cluster sampling. Data from 446 participants (68% females) with mean age 45.3 ± 15 years were used for the analyses. Participants were recruited between March and May. Serum 25-hydroxyvitamin D levels were measured using electrochemiluminescent immunoassay. Results. Vitamin D deficiency was highly prevalent whether using the cutoff of 50 nmol/L or using the more conservative cutoff of 30 nmol/L; more specifically, 71.9% and 39.1% of the study population were deficient using the above cutoffs, respectively In the bivariate analyses, gender, BMI and body fat mass, socioeconomic factors (income and education level), alcohol consumption, dietary intake of fat and of vitamin D, serum LDL-cholesterol, and serum creatinine were all associated with vitamin D status. After adjustment for multiple covariates, age, income, alcohol consumption, and serum creatinine were independent predictors of vitamin D deficiency. Conclusion. Vitamin D deficiency is highly prevalent in Lebanon. Preventive measures should target the modifiable risk factors.